Heterostructure SnO2/g-C3N4 nanoparticles for enhanced visible-light Photodegradation harmful substances in sewage - Yao Xu (Catalysis Communications, 2022)
Hydrothermal synthesis was used to synthesize SnCNx photocatalysts with different SnO2 content. The SnCN4 photocatalyst has a well photocatalytic degradation efficiency for pollutants under visible light irradiation. Rising photoactivity may be related to the synergistic effect between SnO2 and g-C3N4, which leads to an increase in visible light absorption. The interface interaction between the two components promotes effective charge transfer, thereby increasing visible light absorption. The ·O2¯ and ·OH are the main reaction species in the degradation reaction and we also discussed the possible mechanism of this process.